PERANCANGAN APLIKASI ADMINISTRASI ANGGARAN PROYEK PEMBANGUNAN PADA CV RIZKY BAJA RINGAN MENGGUNAKAN VBA EXCEL - Yudin (2022)
Research conducted on CV. Rizky baja ringan aims to improve the process of project budget administration. This company is still processing costs using calculations and writing budgets in the project cost budget book which has considerable risk due to the vulnerability of miscalculation and damage or loss. The design of this budget administration recommendation application is made to reduce the risk of miscalculation, storage, and make it easier for employees to recommendations for development project budget administration. In developing this system the author uses the waterfall method, where this method has steps such as problem identification, system design, system implementation in the program, overall system test, and system maintenance. The proposed system design is in the form of an application for a development project budget administration on CV. Rizky baja ringan who can assist the company in making a budget plan report. The results of the application feasibility study reached 89.99%. This shows that this application is appropriate.